A vacuum lyophilization and bacterial tablet-based method for culture medium evaluation and potential use in probiotic products - Cui, Wen; Zhao, Liang; Shi, Yuwen; Feng, Wei; Chen, Xiao; Liu, Hui (Frontiers in Microbiology, 2025)
IntroductionThe fundamental step in microbiological detection is the preparation of culture medium. The reliability and accuracy of microbiological assay heavily relies on this step. Currently in China, the most recognized standard method for such medium evaluation is ISO 11133-2014. However, this method requires highly complicated biosafety management, detailed standard strains record-keeping and substantial working time.Methods and resultsBacterial tablet is considered to be a novel strategy for bacteria culture medium evaluation. The filter membrane as a carrier ensures uniform cell dispersion, forming a singular colony that can facilitate counting. We examined the viability and storage durability of vacuum freeze-dried bacterial tablets using a filter membrane as a carrier and utilized the results to evaluate culture medium. We found that the recipe GBSS (Glycerinum, Brain Heart Infusion, Sucrose, Sodium Glutamate) showed the highest survival rate for Escherichia coli in vacuum freeze-drying. As a qualified medium, the productivity of target bacterium should be greater than 0.7. A comparison of freeze-dried bacterial tablet method with ISO 11133-2014 quantitative method showed the sensitivity and specificity of this novel method were 94.1% and 88.9% respectively. The results suggested that vacuum freeze-dried bacterial tablet method had high conformity when compared to ISO 11133-2014 quantitative method (χ2 = 0.25, p > 0.05; Kappa = 0.75).DiscussionHence, vacuum freeze-drying method is an integral part of preservation of bacterial strains and the preparation of related biological products. In conclusion, we have developed a novel and effective disposable product for estimating efficiency of the culture medium.